Histopathology Reviews and Recent Advances - Poblet Martinez, Enrique (IntechOpen, 2012)
This edition aims to present some relevant topics in the histopathology area that may be of interest for medical doctors and for other professionals interested in pathology. Histopathology applies basic knowledge obtained from biologic and anatomic science to make diagnosis, to determine the severity and progress of a condition and to evaluate the possible response to certain therapies. Thus, it is not surprising that this discipline constantly expands with progresses produced in biology. In addition, novel technologies that have been recently incorporated, and the adoption of the histopathological methods by different areas, contribute to enlarge the fields that may apply the histopathological methodology. The papers selected for this book comprise a cross-section of topics that reflect the variety of perspectives that histopathology contemplates. Selected representative reviews of topics that are considered relevant or introduce novel concepts are included in this book.